PENGEMBANGAN VIDIO EDUKASI BERBASIS MODEL PEMBELAJARAN TaRL UNTUK MENANAMKAN PEMAHAMAN PESERTA DIDIK DENGAN KENDALA SLOW LEARNING PADA PENDIDIKAN INKLUSI SD NEGERI 1 MELAYU - Lestari, Citra; Sri Hardiningsih, Anggih Tri Cahyadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Bahasa Indonesia, as a key subject in elementary school, plays a vital role in developing students’ literacy skills, especially reading comprehension. However, slow learner students often struggle to grasp lesson content due to cognitive limitations. This study aimed to develop an educational video based on the “Teaching at the Right Level (TaRL)” approach that is valid, practical, and effective in improving reading comprehension among slow learners in Bahasa Indonesia learning. The study was conducted at SD Negeri 1 Melayu with 10 slow learner students. The research employed the “Research and Development (R&D)” method using the Borg and Gall model, comprising six stages: “potential and problems, data collection, product design, product validation, design revision, and product testing”. Validation results showed an average score of 85% from media experts and 84.62% from content experts, indicating the media is highly feasible. Practicality tests revealed very positive responses from teachers (100%) and students (93.33%), classifying the media as very practical. Effectiveness tests demonstrated an increase in learning outcomes, with the average pre-test score rising from 40.25 to 73.5 in the post-test. Therefore, the TaRL-based educational video is proven to be a valid, practical, and effective tool in enhancing the reading comprehension skills of slow learner students in Bahasa Indonesia learning.